MENYELAMI HARAPAN DI TENGAH BAYANG-BAYANG KERESAHAN KERJA (Studi Pada Kantor Sekretariat Daerah Kabupaten Grobogan) - Pradana, Johan; Nugraheni, Rini (Diponegoro Journal of Management, 2021)
ABSTRACT The contract system in terms of employment is often associated with various weaknesses and problems, relating to work relations such as low wages, limited benefits, no job security, and many more. This system also has the potential to cause losses from the workers side and more profits from the employers side. This study aims to understand and find out how the working conditions experienced by contract workers in government agencies are often referred to as "honorer", as well as started from various social phenomena or situations that discuss a lot of problems that are detrimental to employees. Then this research will prove whether the feeling of worries about the sustainability of work in the future (Job Insecurity) is also experienced by the honorary, along with the impact of these feelings, whether it affects the individual or the organization. The last objective is to find out what are the reasons and motivations that underlie employees choosing to work and remain as honorary status full of weaknesses and job insecurity.